Experimental investigation on compressive behavior of corroded thin-walled CHS T-joints with grout-filled GFRP tube repairing. (June 2022) - Zuo, Wenkang; Chang, Hongfei; Li, Zhaowei; An, Aichen; Xia, Junwu; Yu, Tao
Abstract: This paper presents the compression tests of grout-filled GFRP-repaired chord-corroded CHS T-joints. A total of eight specimens, including uncorroded or corroded bare steel joints, grout-filled GFRP- or PVC-repaired joints were tested under axial compressive loading via the brace. The design parameters included the brace-to-chord diameter ratio, weight loss ratio due to corrosion, steel bar anchors on chord and material of external tube. The corrosion and repairing process of specimens are presented, followed by analysis of typical test results such as the failure modes, compressive strength and initial stiffness. The test results indicated that the uniform corrosion with 10% chord weight loss did not change the failure mode of compressive CHS T-joints, but caused near 20% decrease of the compressive strength and the initial stiffness. The strength of external tube and brace diameter were two key factors that guarantee the repairing effect, and the effect of steel bar anchors on chord was minimal. The grout-filled GFRP tube is effective to strengthen chord-corroded CHS T-joints for enhanced compressive strength and stiffness, with the enhance ratio of over 2.0. The repairing mechanism of the grout-filled GFRP tube is to provide a strong constraint effect on the chord, which changes the failure mode of the specimens from chord face plastification to combined failure of chord punching shear and plastification. A modified formula is proposed for estimating the confinement effect of the grout-filled GFRP tube repaired specimens. Highlights: Grout-filled GFRP tube technique was proposed to repair the corroded CHS T-joint. Repairing effect of the grout-filled GFRP tube is demonstrated experimentally. The mechanism of the grout-filled GFRP tube repairing is to provide a strong constraint effect on the chord, and thus changes the failure mode of the chord from surface plastification to combined failure of chord punching shear and plastification. A modified model for estimating the confinement effect of grout-filled GFRP-repaired chord-corroded CHS T-joints was proposed.